2012
DOI: 10.1177/0961203312451200
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of cytokines (TNF-α, IFN-γ), serum profiles of IL-17 and IL-23 in paediatric systemic lupus erythematosus

Abstract: In this preliminary study, we observed a persistent, strong pro-inflammatory cytokine milieu in pSLE patients which reflects ongoing inflammatory damage in different organs. The gene expression profile of these cytokines may be used for assessing organ involvement in pSLE. IL-17 may also serve as a prognostic marker in pSLE. However, longitudinal studies on treatment of naïve patients are required to corroborate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 36 publications
9
54
1
2
Order By: Relevance
“…In the ALPS and DALD patients, the defective function of Fas may further increase this resistance to apoptosis and may favor the expansion of this T-cell subset and the increased levels of IL-17s, which may in turn favor the development of autoimmunity. This mechanism may also play a role in other autoimmune diseases because high levels of IL-17 similar to that detected in our patients have been described in SLE, 24,28 RA, 29,30 and psoriasis. [31][32][33] Moreover, decreased Fas function has been also detected in patients displaying autoimmune diseases different from ALPS and DALD.…”
Section: Discussionsupporting
confidence: 86%
“…In the ALPS and DALD patients, the defective function of Fas may further increase this resistance to apoptosis and may favor the expansion of this T-cell subset and the increased levels of IL-17s, which may in turn favor the development of autoimmunity. This mechanism may also play a role in other autoimmune diseases because high levels of IL-17 similar to that detected in our patients have been described in SLE, 24,28 RA, 29,30 and psoriasis. [31][32][33] Moreover, decreased Fas function has been also detected in patients displaying autoimmune diseases different from ALPS and DALD.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to IL-17, IL-23 was also found to be crucial for the development of various autoimmune diseases in murine models [4042] and in humans [43] by promoting Th17 cell–mediated tissue inflammation. There is accumulating evidence indicating the importance of IL-23 in patients with SLE [4446]. Of note, our group has shown that clinical and pathology findings of LN are mitigated in lupus prone mice with IL-23 receptor deficiency [47] or treated with an anti-IL23 antibody [48].…”
Section: Il-17 In Slementioning
confidence: 99%
“…Studies have shown different cytokine profiles for Th1, Th2, Th17, and Treg cells in adult SLE patients compared to a healthy control group, as well as differences in disease phenotype and activity (712). However, only a few studies have investigated the cytokine profile of cSLE (1316). Therefore, we conducted a cross-sectional and longitudinal study to determine the profiles of IL-2, IL-4, IL-6, IL-10, IL-17A, IFN-γ, and TNF cytokines in cSLE patients and a healthy control group, and evaluated the association of these cytokines with disease activity.…”
Section: Introductionmentioning
confidence: 99%